Effect of energy supply on amino acid utilization by growing steers - Schroeder, Guillermo Fernando (Kansas State University, 2006)
Effects of energy supply on the efficiency of methionine and leucine utilization in growing steers were evaluated in 3 studies. We hypothesized that increased energy supply would improve efficiency of amino acid utilization. In study 1, treatments were abomasal infusion of 0 or 3 g/d of L-methionine and supplementation with 3 amounts of energy (0, 1.3, and 2.6 Mcal GE/d) in a factorial design. Nitrogen balance was increased (P<0.05) by methionine supplementation and increased linearly (P<0.05) with energy supply, indicating that efficiency of methionine use was improved by energy supplementation. In study 2, the effects of supplementation with no energy or isocaloric (1.3 Mcal GE/d) supplementation with glucose, fat, acetate, or propionate at 2 levels of L-methionine supplementation (0 or 3 g/d) were evaluated. Supplemental energy increased (P<0.01) nitrogen retention, without differences among energy sources. The results indicated that energy supplementation improved the efficiency of methionine utilization, independent of energy source. In study 3, effects of energy supplementation on leucine utilization in growing steers at 2 body weights (150 kg in Exp. 1 and 275 kg in Exp. 2) were evaluated. Treatments were a 3 Ã 2 factorial with 0, 4, or 8 g/d of L-leucine infused abomasally and 2 amounts of energy (0 and 1.9 Mcal GE/d). In Exp. 1, nitrogen retention linearly increased in response to leucine supplementation when additional energy was supplied. When no energy was supplemented, nitrogen retention was similar for 4 and 8 g/d of leucine. Energy supplementation increased nitrogen retention (P<0.01), indicating that energy supplementation improved the efficiency of leucine utilization by modestly increasing nitrogen retention when leucine was limiting and by increasing the ability of steers to respond to the highest amount of supplemental leucine. In Exp. 2, nitrogen retention was not affected by leucine supplementation, indicating that leucine did not limit protein deposition. Energy supply increased nitrogen retention (P<0.01) independent of the level of leucine supplemented, demonstrating an increase in capacity for protein deposition when energy was supplemented. Overall, our results indicated that energy affects the efficiency of amino acid utilization, challenging the assumption of a constant efficiency of use.
Keywords: Amino acid; Energy; Utilization; Growth; Steer; Nutrition; Agriculture, Animal Culture and Nutrition (0475)